Becoming Reflective and Inquiring Teachers: Collaborative Action Research for In-service Chilean Teachers - Martine Pellerin; Fraño Ivo Paukner Nogués (Universidad Autónoma de Baja California, 2015)
This article discusses the outcomes of a case study that engaged Chilean in-service teachers in systematic action research (AR) as a means of improving their pedagogical practice and effecting changes in their educational context. The study involved six in-service teachers from a region of Chile and two university researchers. The findings show that knowledge of systematic AR provided the teachers with the necessary means to engage in a critical reflection and inquiry process regarding their own practice. The teacher participants also perceived the self-reflective spiral of reflection and action to be crucial in establishing new habits of inquiry and reflection about their own pedagogical actions. The findings support earlier studies (e.g., Price & Valli, 2005; Steven & Kitchen, 2005, 2011) concerning the necessity of including knowledge of systematic AR in teacher preparation programs in order to foster strong habits of inquiry and reflection among preservice teachers. Finally, the study suggests that participation in a systematic reflection and inquiry process contributes to empowering in-service teachers to become agents of pedagogical change through their own actions.